The Penta-helix: A sustainable tourism strategy of Bali's villages - Khusnul Rofida Novianti (Jurnal Inovasi Ekonomi, 2020)
The study proposes a sustainable tourism strategy in Bali’s village. This paper is qualitative research using content analysis based on secondary data and applies the Penta-helix approach. Based on the literature review and synthesis, the paper argues that integrating the academic and private sectors through research, social services, and CSR is the primary booster to accelerate sustainable village tourism in Bali, especially for recovery after the COVID-19 outbreak.